2016
DOI: 10.31989/ffhd.v6i10.296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some Tropical Eggplant Fruits (Solanum Spp) Supplemented Diet On Diabetic Neuropathy In Experimental male Wistar Rats In-vivo

Abstract: Background: Solanum known as eggplant is a popular vegetable crop grown in the subtropics and tropics. Eggplant is a perennial but grown commercially as an annual crop. The fruits of eggplant is primarily used as a cooking vegetable for various dishes. Eggplant   comes in various kinds of species, which are highly variable for its fruit colour, as well as shape and size.Content and Purpose of this study: This study focused on comparing the effect of dietary African eggplants (AP) Solanum kumba,(PG) Solanum gil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…In the same vein, the inclusion of the tropical eggplant in the diet could restore and reverse the diabetic state of the diabetic model due to the presence of polyphenol and flavonoid constitutes as reported earlier by Nwanna et al. (, ) from the high‐performance liquid chromatogram, which depicts the individual phenolic acids and flavonoids. It was reported that the concentration of these constituents was more in S. kumba, which could have contributed to the observed activities.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In the same vein, the inclusion of the tropical eggplant in the diet could restore and reverse the diabetic state of the diabetic model due to the presence of polyphenol and flavonoid constitutes as reported earlier by Nwanna et al. (, ) from the high‐performance liquid chromatogram, which depicts the individual phenolic acids and flavonoids. It was reported that the concentration of these constituents was more in S. kumba, which could have contributed to the observed activities.…”
Section: Discussionsupporting
confidence: 71%
“…The methods of Oboh and Ogunruku (2010), Srinivasan, Viswanad, Asrat, Kaul, and Ramara (2005), and Nwanna et al. () were used for the formulation of the food and the experimental design. Induction of rats to make them diabetic and the grouping were done according to the earlier studies reported by Nwanna et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Nwanna, Ibukun, and Oboh (, ) and Anosike, Abonyi, and Ubaka () revealed an abundance of vitamin C, polyphenols and flavonoids in the local garden egg/eggplants with anti‐diabetes, anti‐ulcer properties. The report from Nwanna, Ibukun, et al () also confirmed that the inclusion of these eggplant fruits as part of the dietary composition could reduce the blood glucose level to 22%–50% lower than the hyperglycemia‐induced diabetes using an in vivo model. Studies on the neuroprotective property from the tropical eggplant in hyperglycemia‐mediated neurodegeneration are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It is the most important of the vegetable families which are essentially tropical in origin (Nwanna et al, 2013). Most species are wild but some of them such as S. aethiopicum, S. macrocarpon, S. kumba and S.gilo bear edible fruits in West African origin (Nwanna et al, 2016). Its fruits may be consumed freshly raw, dry or cooked.…”
Section: Introductionmentioning
confidence: 99%